A portable device for water-sloshing-based electricity generation based on charge separation and accumulation - Jihoon Chung; Deokjae Heo; Kyunghwan Cha; Zong-Hong Lin; Jinkee Hong; Sangmin Lee (iScience, 2021)
Summary: Hydropower generation is a well-known electricity generation technique that uses Faraday's law and hydraulic turbines. Recently, a triboelectrification-based electricity generation device, using water as the triboelectric material (W-TEG) was developed. In addition to the enhancement of the electrical output performance through the operation mechanism, the characteristics of the W-TEG must be examined at the design level to facilitate its portable application. Therefore, in this work, we developed a portable water-sloshing-based electricity generator (PS-EG) that can produce a high electric output and achieved its closed-loop circuit design and quantitative analysis for portable applications. The proposed PS-EG produced peak open-circuit voltage (VOC) and closed-circuit current (ICC) of up to 484 V and 4.1 mA, respectively, when subjected to vibrations of 2 Hz. The proposed PS-EG can be effectively used as an auxiliary power source for small electronics and sensors.